Knowledge and attitudes among dental students about COVID-19 and its precautionary measures: a cross-sectional study - Alawia Ruwaa; Riad Abanoub; Kateeb Elham (EDP Sciences, 2021)
Objective: This study aims to evaluate students' knowledge and attitudes about COVID-19 and its precautionary measures. Methods: A cross-sectional study was conducted among dental students in their clinical practice years in two Palestinian universities. An online questionnaire was sent out using students' in mid-May, 2020. The questionnaire assessed students self-reported knowledge about the COVID-19, and students' attitudes towards providing clinical care during the pandemic. Results: A total of 305 dental students completed the questionnaire. Fifty-nine percent (n = 180) reported having updated training on infection control measures in dental settings and 29% (n = 89) reported having attended a training course regarding COVID-19. Eighty-two percent of students (n = 250) preferred to avoid working with suspected COVID-19 patients. Almost 89% (n = 269) admitted fear of transmitting the virus to their families. This fear was related to their perception that using regular standard precautions is unsafe in dealing with COVID-19 patients and their perception of their schools' preparedness to update infection prevention measures (χ2 = 50.45, p < 0.001) (χ2 = 9.77, p = 0.021). Conclusion: Students in this sample are aware of COVID-19 and its precautionary measures. Adherence to new, stricter infection control protocols and periodic orientation of students to these protocols are ways to guarantee a safer environment for both patients and students.